In vitro and in vivo pharmacological characterization of a neuropeptide S tetrabranched derivative. Issue 1 (5th January 2015) - Ruzza, Chiara; Rizzi, Anna; Malfacini, Davide; Pulga, Alice; Pacifico, Salvatore; Salvadori, Severo; Trapella, Claudio; Reinscheid, Rainer K.; Calo, Girolamo; Guerrini, Remo
Abstract The peptide welding technology (PWT) is a novel chemical strategy that allows the synthesis of multibranched peptides with high yield, purity, and reproducibility. With this approach, a tetrabranched derivative of neuropeptide S (NPS) has been synthesized and pharmacologically characterized. The in vitro activity of PWT1‐NPS has been studied in a calcium mobilization assay. In vivo, PWT1‐NPS has been investigated in the locomotor activity (LA) and recovery of the righting reflex (RR) tests. In calcium mobilization studies, PWT1‐NPS behaved as full agonist at the mouse NPS receptor (NPSR) being threefold more potent than NPS. The selective NPSR antagonists [tBu‐D‐Gly5]NPS and SHA 68 displayed similar potency values against NPS and PWT1‐NPS. In vivo, both NPS (1–100 pmol, i.c.v.) and PWT1‐NPS (0.1–100 pmol, i.c.v.) stimulated mouse LA, with PWT1‐NPS showing higher potency than NPS. In the RR assay, NPS (100 pmol, i.c.v.) was able to reduce the percentage of mice losing the RR after diazepam administration and their sleep time 5 min after the i.c.v. injection, but it was totally inactive 2 h after the injection. On the contrary, PWT1‐NPS (30 pmol, i.c.v.), injected 2 h before diazepam, displayed wake‐promoting effects. This PWT1‐NPS stimulant effect was no longer evident in mice lacking the NPSR receptor. The PWT1 technology can be successfully applied to the NPS sequence. PWT1‐NPS displayed in vitro a pharmacological profile similar to NPS. In vivo PWT1‐NPS mimicked NPS effects showing higher potency and long‐lasting action.